Soliloqui : pemikiran filsafat, agama, dan politik - Ma'ruf, Ade, 1975-; Alimi, Anas Syahrul (Yogyakarta : Jendela, 2002)
Politics, religion in Indonesia; collection of articles.
Bibliography : p. 171-174
Keywords: Islam -- Indonesia; Islam and politics -- Indonesia; Indonesia -- Politics and government -- 1998-